Current Publication Lags in Economics Journals - Yohe, Gary (Journal of Economic Literature, 2016)
PHE ECONOMICS PROFESSION depends, to a large degree, upon its scholarly journals to disseminate the results and applications of its recently completed research. The Journal of Economic Literature is, in fact, evidence of that dependence; much of the contents of each issue is devoted to an indexing of the current articles to facilitate both access to primary sources and quick cross-referencing with related material. But how recent are the results reported in the current literature? How long does it usually take for a piece of research to evolve from a submitted manuscript to a published article? To my knowledge, only one study has confronted this question directly, and it was published nearly 15 years ago. In that study, Robert Coe and Irwin Weinstock (1967, p. 40) reported an average lag between submission and publication of 250 days (8.2 months) for articles published in 1966. What has happened since? There are no formal surveys to support the suspicion, but there is evidence to suggest that the lags have actually increased. Some journals have begun to charge submission fees ostensibly to reduce the number of manuscripts they must review. A plethora of specialized journals have emerged to provide new outlets for specialized papers and to relieve some of the burden from the traditional journals of more general scope. One new journal, Economics Letters, has been founded completely in response to the lag problem; it publishes short papers as quickly as possible in an effort to distribute at least the thrust of current research without a prolonged waiting period. All of these responses to long lags lead to one question: how severe are the current lags between submission and publication? This brief note will report on the results of a survey that can begin to assess the current magnitude of the lag problem, the major components of that problem, and the success of the various efforts to alleviate it. Information about the lags involved in the 40 most recently published articles in each journal was solicited from the editors of 66 journals whose contents are routinely recorded in the JEL. Twenty editors responded directly to the request, and their reports formed the foundation of this study. Seven other journals were also in-